Transcriptome sequencing, and rapid development and application of SNP markers for the legume pod borer Maruca vitrata (Lepidoptera: Crambidae). - Venu M Margam; Brad S Coates; Darrell O Bayles; Richard L Hellmich; Tolulope Agunbiade; Manfredo J Seufferheld; Weilin Sun; Jeremy A Kroemer; Malick N Ba; Clementine L Binso-Dabire; Ibrahim Baoua; Mohammad F Ishiyaku; et al. (PLoS ONE)
The legume pod borer, Maruca vitrata (Lepidoptera: Crambidae), is an insect pest species of crops grown by subsistence farmers in tropical regions of Africa. We present the de novo assembly of 3729 contigs from 454- and Sanger-derived sequencing reads for midgut, salivary, and whole adult tissues of this non-model species. Functional annotation predicted that 1320 M. vitrata protein coding genes are present, of which 631 have orthologs within the Bombyx mori gene model. A homology-based analysis assigned M. vitrata genes into a group of paralogs, but these were subsequently partitioned into putative orthologs following phylogenetic analyses. Following sequence quality filtering, a total of 1542 putative single nucleotide polymorphisms (SNPs) were predicted within M. vitrata contig assemblies. Seventy one of 1078 designed molecular genetic markers were used to screen M. vitrata samples from five collection sites in West Africa. Population substructure may be present with significant implications in the insect resistance management recommendations pertaining to the release of biological control agents or transgenic cowpea that express Bacillus thuringiensis crystal toxins. Mutation data derived from transcriptome sequencing is an expeditious and economical source for genetic markers that allow evaluation of ecological differentiation.